Support Workshop Enhancement Readiness and The Response of The Nahdlatul Ulama Hospital Against Covid-19 and Infectious Diseases New Other - Umi Hanik; Agus Aan Adriansyah; Akas Yekti Pulih Asih; Budhi Setianto; Iqbal Firdaus; Muhammad Zahid Abdillah; Nikmatus Sa’adah (Universitas Andi Djemma, 2023)
Until October 2, 2021, the total number of cases of Covid-19 confirmation in the world is 234.110,530 cases with 4,788,697 deaths (Case Fatality Rate 2.0%) in 204 infected countries and 151 Transmission Countries communities. Government The Republic of Indonesia has reported 4,218,142 confirmed people positive for COVID-19 and there were 142,115 deaths (CFR: 3.4 %) related to COVID-19 reported and 4,042,215 patients have healed from the disease. Since Covid-19 was declared a pandemic, various efforts have been conducted by the government with Support cross-sectoral, as efforts increase knowledge power health in the environment Association House Islamic Hospital Nahdlatul Ulama, ARSINU together LETTERA Foundation organizes support workshop enhancement readiness and Nahdlatul Hospital response Ulama (NU) against Covid-19 and disease infectious new others, workshops held online and off this line followed by 183 participants held at the Surabaya Islamic Hospital Workshop involving 5 houses sick in ARSINU 's shade grabbed enthusiastically by participants, workshops held with this hybrid method increase participants ' knowledge go on by 20%, expected through this workshop whole power health capable give good contribution on implementation daily officer power health walk right his job in giving service to patient covid 19 and capable control self for infected Covid-19.